Political polarization: A quantitative approach to the phenomenon in Argentina - Ivickas Magallan, Maximiliano (2026)
This work aims to analyse political polarization in Argentina during the period 1993-2019. The phenomenon is approached from a multidimensional perspective that considers the historical, theoretical, and practical aspects of the phenomenon. To achieve this, we consider political cleavages, local party dynamics, and the prevailing presidential system in the country. The hypothesis being considered is that political polarization is a phenomenon that ought to be examined within the institutional rules of a country's democratic system, while also considering the impact of historical political processes upon it. Data collection is based on a combination of primary and secondary sources, utilizing both qualitative and quantitative methods to compile and analyse the attitudes of both official and non-official political blocs in legislative decisions. Through this research, we aim to deepen the understanding of political polarization in Argentina, emphasizing its influence on the functioning of democracy and its evolution over nearly three decades. Additionally, we seek to elucidate the role that polarization plays in the political system and how it affects the capacity for consensus in the legislative and executive branches of government.